What is the impact of social health protection on access to health care, health expenditure, and impoverishment?: a comparative analysis of three African countries - Scheil-Adlung, Xenia; Asfaw, Abay; Booyse, Frikkie; Lamiraud, Karine; Reynaud, Emmanuel; Jütting, Johannes; Xu, Ke; Carrin, Guy; Chatterji, Somnath; Evans, David; James, Chris; Muchiri, Stephen (World Health Organization, 2006)
Recently, there is an increasing focus on social health protection via health insurance as a potential promising way to better to deal with health risks in developing countries. However, the empirical basis for a profound analysis of the effects of health insurance is still very thin. Against this background the ILO, WHO, and the OECD Development Centre sponsored by GTZ have undertaken a collaborative research project in this field. This paper summarizes the results of three individual research projects (Asfaw, 2005; Lamiraud et al., 2005; Xu et al., 2005) measuring the impact of membership in a health insurance scheme in three African countries, namely Kenya, Senegal and South Africa. The structure of the paper is as follows. The first section of this paper is briefly outlining the health care systems in Kenya, Senegal and South Africa followed by a short description of the methodology and data used. The later sections focus on empirical results and policy implications.